PENGARUH LAMA KERJA DAN JAM KERJA TERHADAP TINGKAT PENDAPATAN KARYAWAN PADA PT. PELINDO REGIONAL 4 MAKASSAR - Masri, Amanda (Universitas Teuku Umar, 2024)
This study aims to analyze the effect of length of service and working hours on employee income at PT. Pelindo Regional 4 Makassar. The research method used is quantitative with a descriptive approach and multiple linear regression analysis. Data were collected through questionnaires distributed to 53 respondents who are employees of the company. The results of this study indicate that: (1) the variable length of service (X1) has a positive and significant effect on the income level of employees of PT. Pelindo Regional 4 Makassar (Y), with a t- value of 3.148 and a significance of 0.003. (2) the variable hours of work (X2) has a positive and significant effect on the income level, with a t-value of 5.671 and a significance of 0.000.Keywords : Length of Service, Working Hours, Income, Employees, PT. Pelindo.